Exploring the Regulation of Jiangtang Tiaozhi Formula on the Biological Network of Obese T2DM Complicated With Dyslipidemia Based on Clinical Transcriptomics - Bao, Tingting; Wang, Song; Yang, Yingying; He, Lisha; Han, Lin; Zhai, Tiangang; Chen, Jia; Zhou, Qiang; Zhao, Xiyan; Lian, Fengmei; Zhao, Linhua; Tong, Xiaolin (Frontiers in Endocrinology, 2022)
Objective: To use systems biology to explore the biomolecular network mechanism of the JTTZR in the intervention of obese T2DM patients with dyslipidemia. Methods: Twelve patients with obese type 2 diabetes mellitus and dyslipidemia (traditional Chinese medicine syndrome differentiation was excess heat syndrome of the stomach and intestines) were treated with JTTZR for 24 weeks, and 12 patients were included in the healthy control group. First, blood samples from 6 patients in each group (disease group before treatment, disease group after treatment, and healthy control group) were collected for RNA microarray analysis. qPCR was used to validate these target lncRNAs and mRNAs. Finally, a detailed analysis of the differences in the disease group before treatment vs. the healthy control group and the disease group after treatment vs. the disease group before treatment was undertaken. In addition, we focused on disease-related pathways and analyzed the correlation between the differential expression of target lncRNAs and clinical indicators. Results: (1) Disease group before treatment vs. healthy control group: There were 557 up-regulated lncRNAs, 273 down-regulated lncRNAs, 491 up-regulated mRNAs, and 1639 down-regulated mRNAs. GO analysis and pathway analysis showed that T2DM may be related to cell proliferation in the forebrain, post-embryonic organ development, calcium signaling pathway.. qPCR validation showed that the expression of XLOC-005590 and HNF1A-AS1 as target lncRNAs increased, and this was verified by gene chip analysis. (2) Disease group after treatment vs. disease group before treatment: 128 lncRNAs were upregulated, 32 lncRNAs were downregulated, 45 mRNAs were upregulated, and 140 mRNAs were downregulated. GO analysis and pathway analysis showed that JTTZR may treat T2DM through endosome transport, the insulin signaling pathway, and glycine, serine, and threonine metabolism. qPCR validation showed that in the healthy control group, XLOC_005590 was upregulated, whereas the downstream gene (ECI2) was downregulated in the disease group before treatment. However, after 24 weeks of intervention with JTTZR, XLOC_005590 was downregulated and ECI2 was upregulated compared with the disease group before treatment (0 weeks) (P <0.05). Conclusion: JTTZR may interfere in patients with obese T2DM with dyslipidemia by regulating pathways such as fatty acid degradation, glycolysis/gluconeogenesis, and pyruvate metabolism.